Dynamic Agriculture in East Asia: Land-Livelihood Interactions - Zhang, Le; Kono, Yasuyuki (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Subsistence smallholder agriculture in East Asia was highly recognized by Dr. Franklin Hiram King in his book Farmers of Forty Centuries or Permanent Agriculture in China, Korea and Japan though it has been abandoned due to industrialization and urbanization since the end of the 20th century. This reprint consists of research on the transformation of agricultural systems and the mechanism behind these phenomena in China and Japan. We believe that this reprint is practically important, and we appreciate your understanding of the imperfections and hope you enjoy this reprint.